DETECTION OF DISPLACEMENT USING GLASS OPTICAL FIBER SENSOR WITH VARIOUS CONFIGURATION - Lebang, Annamaintin Kobong; Arifin, A; Abdullah, Bualkar (Indonesian Physical Review, 2021)
The research has measured the landslide using a displacement sensor based on Glass Optical Fiber (GOF) and Optical Time Domain Reflectometer (OTDR). The sensor manufacture process consists of various materials, structures, configurations, diameters, and directions. The sensor is made using GOF with a single-mode structure and single mode-multimode-Singlemode (SMS) structure. Each system is given a variety of configurations, namely gamma, bowknot, and three loops configuration. Each arrangement is provided a variation of the indentation diameter in three displacement directions. The test results will be read as the power loss on the OTDR in dB units. The results obtained were then compared between two materials, two structures, and directions. Displacement resulting landslides and changes to the sensor, causing power losses, and affecting the characteristics of each sensor. We found the best measurement results with the sensitivity value of 0.241 dB/mm and the resolution value of 0.004 mm. The displacement sensor has been made for measuring landslide in the laboratory-scale simulation based on GOF and OTDR with easier fabrication, easy operation, high sensitivity, better resolution and can be connected to a computer